The Effect of Rootstock Cultivar and Bud Load on the Colour of Vitis vinifera L. cv. Muscat noir (Red Muscadel) Grapes - Hunter, J.J.; de La Harpe, A. C. (South African Journal of Enology and Viticulture, 2017)
The effects of rootstock cultivar and bud load on colour expression in the grapes of Vi tis vinifera L. cv. Muscat noir were investigated. Different rootstocks had no significant effect on skin colour density of the grapes Grapes from vines with a low bud load (16 buds.vine·’) had the highest skin colour density.